2004
DOI: 10.1139/w04-059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for the concentration ofCryptosporidiumoocysts andGiardiacysts from raw waters

Abstract: This study compared the recovery of Cryptosporidium oocysts and Giardia cysts ((oo)cysts) from raw waters using 4 different concentration-elution methods: flatbed membranes, FiltaMax foam, Envirochek HV capsules, and Hemoflow ultrafilters. The recovery efficiency of the combined immunomagnetic separation and staining steps was also determined. Analysis of variance of arcsine-transformed data demonstrated that recovery of Cryptosporidium oocysts by 2 of the methods was statistically equivalent (flatbed filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
1
17
0
6
Order By: Relevance
“…However, the recovery rates of ova using HFUF from raw wastewater were found to be highly variable (0.3-35%) between the WWTPs. Such discrepancy again could be attributed to the variable solid contents present in wastewater samples in time and space (Simmons et al, 2001;Ferguson et al, 2004). The turbidity of raw wastewater collected from both the WWTPs were much higher (246-286 NTU) than the treated wastewater (86-197 NTU).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the recovery rates of ova using HFUF from raw wastewater were found to be highly variable (0.3-35%) between the WWTPs. Such discrepancy again could be attributed to the variable solid contents present in wastewater samples in time and space (Simmons et al, 2001;Ferguson et al, 2004). The turbidity of raw wastewater collected from both the WWTPs were much higher (246-286 NTU) than the treated wastewater (86-197 NTU).…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the low suspended solid content of treated wastewater making it possible to pass through the membrane using the membrane filtration method. It has been previously reported that ova were better retained on the membranes during filtering of water samples compared to a potential loss of ova during floatation (Nieminski et al, 1995;Ferguson et al, 2004). Because of the high solid contents and turbidity, the membrane filtration method was not suitable for processing raw wastewater and sludge samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations